Geomorphology and substrate of Galway Bay, Western Ireland. Issue 2 (9th December 2020) - McCullagh, Denise; Benetti, Sara; Plets, Ruth; Sacchetti, Fabio; O'Keeffe, Eimear; Lyons, Kieran
ABSTRACT: A combination of multibeam bathymetry and backscatter, LiDAR altimetry and bathymetry, satellite images, and hydrodynamic model outputs were used to map the seafloor and coastline of Galway Bay (western Ireland). This is the first time these multiple datasets have been integrated into a single combined geomorphological and substrate map. The substrate of the bay is predominantly mud and sand with bedrock outcropping extensively around the coastline. The main depositional features are dunes, while the main erosional features are scours and outcropping bedrock. Hydrodynamic model outputs show good correlation between the direction and intensity of prevailing currents and the location and shape of the features in the bay. This indicates that although Galway Bay was shaped glacially through the passage of the British-Irish Ice Sheet across the bay and ensuing glacial and marine sediment deposition, many of the mapped seafloor landforms are modern and current-induced.